Parental Strategies for Stimulating Speech Skills in Young Children - Ikromah, Ikromah; Pahrul, Yolanda; Nur, Maulida; Risna, Inten (Sekolah Tinggi Ilmu Tarbiyah (STIT) Ahlussunnah Bukittinggi, 2025)
Speaking ability is an important aspect of early childhood development because it forms the basis of communication, learning, and social interaction. This study aims to describe parental strategies for stimulating speaking skills in early childhood and to identify the factors that influence them. The study used a qualitative method with a case study approach conducted in an early childhood education setting. Data were obtained from three informants, namely parents and their 6-year-old children with speech delays. Data were collected through observation, in-depth interviews, and documentation, then analyzed thematically. The findings indicate that parental strategies for stimulating children's speaking skills include creating a pleasant communication environment, reading stories, singing together, role-playing, using visual media such as picture cards and posters, and repeating words to practice pronunciation. Singing and playing were found to be the most effective methods because children enjoyed them and they facilitated the acquisition of new vocabulary. Factors that hinder speech development include limited interaction time due to parents' busy schedules, excessive use of electronic devices, lack of communication with peers, the habit of using “baby talk,” the child's health condition, and hereditary factors. These findings confirm that consistent, varied stimulation tailored to children’s interests is crucial for speaking development during the Golden Age period. The study recommends collaboration between parents and early childhood education institutions in providing a language-rich environment and limiting the use of electronic devices.